PEMBERATAN SANKSI PIDANA TERHADAP PELAKU ILLEGAL LOGGING DALAM PUTUSAN HAKIM PADA PUTUSAN NEGERI MAJALENGKA NO.155/PID.SUS/2019/PN.Mjl - Olivia Priscilla (Jurnal Hukum Adigama, 2021)
Illegal logging is an act of criminal that covers actions such as harvesting, processing, and buying or selling timber that undermines the legitimacy and the various losses from this action also threaten human’s life resources. Loss include not only economical damage, but also result in the loss of those priceless lives. In Article 1 Number 2 of Law Number 18 of 2013 about Prevention and Eradication of Forest Destruction outline that forest territory is a certain region that is determine by the government to maintain its existence as permanent forest. But In reality, many criminal actions of destroying forest without an official permission occur which can be punished with imprisonment or fine which has been set in Article 12 Section 1 of Law Number 18 of 2013 about Prevention and Eradication of illegal Forest Destruction, is no longer a small matter. Because the existence of forests is very important and provides benefits for all people, of course forests in Indonesia must be protected by law. But in reality, in carrying out forest protection efforts, not all communities are aware of the importance of forest preservation, so that forest protection efforts are only carried out by people or organizations that tend to be aware of forest sustainability. Implementation of forest protection is lacking. For example in the Majalengka State Decision Number 155/Pid.Sus/PN.Mjl where there are people who ignore the law of the forest protection for their own interests and benefits.